Peran Adat dalam Penentuan Status Kewarganegaraan : Studi Kasus Masyarakat Adat di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Ibnu Hibban; Aura Ardhana Novia; Hasna Raissa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the role of customary law in determining citizenship status in Indonesia, with a particular emphasis on how customary law interacts with the state legal system and how this impacts Indigenous communities. Indigenous communities often face administrative issues, such as the process of citizenship registration and access to public services, due to the misalignment between uniform state laws and traditional local customary laws. This study found the main issues faced by indigenous communities in Indonesia, such as legal uncertainty and social marginalization. This research aims to comprehensively study the influence of customary law on the determination of citizenship status in Indonesia and to compare it with experiences in other countries. The research method used is normative, doctrinal, or library research method. This study provides information on how to improve the integration between customary law and state law to create a citizenship system that is fairer and more inclusive for Indigenous communities. Reducing inequality and increasing the participation of indigenous communities in social and political life is expected through policy reforms that take into account the needs of indigenous peoples.